"I'm (Not) Offended by Whom I See!" The Role of Culture and Model Ethnicity in Shaping Consumers' Responses toward Offensive Nudity Advertising in Asia and Western Europe. Issue 1 (25th April 2022) - Terlutter, Ralf; Diehl, Sandra; Koinig, Isabell; Chan, Kara; Tsang, Lennon
Abstract: Based on culture identity theory and schema theory, we investigate how model ethnicity influences the perception and effectiveness of potentially offensive nudity advertising in Asia and Western Europe. Study 1 with 5, 193 ad evaluations by 1, 731 subjects from two countries shows that the overall perceived offensiveness in nudity advertising was higher in Asia (China) than in Western Europe (Austria). While previous research indicates that same-ethnicity endorsers are typically favorable for advertising outcomes, our study demonstrates that same-ethnicity endorsers in nudity advertising led to a higher perceived offensiveness and more negative advertising outcomes in Asia, as compared to endorsers of other ethnicities. In Western Europe, in contrast, same-ethnicity endorsers led to a lower perceived offensiveness and more positive advertising outcomes. A follow-up experiment with 373 subjects validated the results. We suggest a model of multi-ethnic offensive nudity advertising effects that is tested with structural equation modeling. Our findings have implications for international advertising theory and international advertising practice.